2010
DOI: 10.1104/pp.109.151142
|View full text |Cite
|
Sign up to set email alerts
|

Combined Bimolecular Fluorescence Complementation and Förster Resonance Energy Transfer Reveals Ternary SNARE Complex Formation in Living Plant Cells

Abstract: Various fluorophore-based microscopic methods, comprising Fö rster resonance energy transfer (FRET) and bimolecular fluorescence complementation (BiFC), are suitable to study pairwise interactions of proteins in living cells. The analysis of interactions between more than two protein partners using these methods, however, remains difficult. In this study, we report the successful application of combined BiFC-FRET-fluorescence lifetime imaging microscopy and BiFC-FRET-acceptor photobleaching measurements to vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 54 publications
2
45
0
Order By: Relevance
“…In barley (Hordeum vulgare), PIP2 colocalized in ROR2/SYP121 vesicle-like compartments, supporting this hypothesis (Kwaaitaal et al, 2010). We report here that the SYP121-Sp2 from Arabidopsis and its putative ortholog from maize affect the delivery of Zm-PIP2;5 to the plasma membrane in maize mesophyll protoplasts and epidermal cells.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…In barley (Hordeum vulgare), PIP2 colocalized in ROR2/SYP121 vesicle-like compartments, supporting this hypothesis (Kwaaitaal et al, 2010). We report here that the SYP121-Sp2 from Arabidopsis and its putative ortholog from maize affect the delivery of Zm-PIP2;5 to the plasma membrane in maize mesophyll protoplasts and epidermal cells.…”
Section: Introductionsupporting
confidence: 69%
“…For the photobleaching method, three images were acquired for both the mCFP and mYFP channels, and then the mYFP was bleached by 80 iterations with fullpower laser illumination, while the fluorescence intensity of the mCFP was simultaneously monitored along time. The FRET efficiency (E) was determined according the equation E = 12 I DA /I D , where I DA is the intensity of the donor fluorescence before photobleaching and I D the fluorescence intensity of the donor after photobleaching, as described elsewhere (Kwaaitaal et al, 2010). The sensitized emission method was used on a subpopulation of tobacco epidermal cells and protoplasts to confirm the data obtained by acceptor photobleaching.…”
Section: Confocal Microscopymentioning
confidence: 99%
“…SYP61 has thus far been considered solely as a TGN resident, with no involvement in anterograde transport to the PM. It has been shown that the SYP121 Qa-SNARE PM resident (PEN1) [51] interacts with the SNAP33 adaptor and the two functionally redundant VAMP72 synaptobrevins [52] in forming the PEN1-SNAP33-VAMP721/VAMP722 tertiary SNARE complex that contributes to a fungal resistance system [52,53]. In the leaf epidermis, VAMP722-GFP vesicles accumulate in intracellular compartments in response to an infection by Blumeria graminis.…”
Section: Syp61 Facilitates the Trafficking Of Proteins To The Pmmentioning
confidence: 99%
“…Additionally, the CFP-HDA19 and YFP-SNL1 fusion vectors were constructed to confirm the fusion protein localization with pENSG-CFP and pENSG-YFP, respectively (Kwaaitaal et al, 2010). For transient expression, Agrobacterium strains (GV3101 pm90RK) carrying the constructs were used (Clough and Bent, 1998) for infiltration of 5-to 6-week-old Nicotiana benthamiana leaves.…”
Section: Interaction Between Snl1 and Hda19 By Plant Bifcmentioning
confidence: 99%